Model Kesiapan Berwirausaha (Literature Review) - Gupron, Gupron; Yandi, Andri; Maharani, Amalina (Siber Nusantara Publisher, 2023)
Abstract: Literature articles reviewing factors that influence entrepreneurial readiness are scientific articles that aim to build a research hypothesis on the influence of variables to be used in further research, within the scope of management science. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are that: 1) Creativity influences entrepreneurial readiness; 2) Self-efficacy influences entrepreneurial readiness; and 3) entrepreneurial motivation influences entrepreneurial readiness. Apart from these 3 exogenous variables, there are many other factors which influence entrepreneurial readiness which include entrepreneurial knowledge, internship experience, role of parents, and interest in entrepreneurship. Abstrak: Artikel literatur review faktor-faktor yang mempengaruhi kesiapan berwirausaha adalah artikel ilmiah yang bertujuan membangun hipotesis riset pengaruh antar variabel yang akan digunakan pada riset selanjutnya, dalam ruang lingkup ilmu manajemen. Metode penulisan artikel Literature Review ini adalah dengan metode library risearch, yang bersumber dari media online seperti Google Scholar, Mendeley dan media online akademik lainnya. Hasil artikel Literature Review ini adalah bahwa: 1) Kreatifitas berpengaruh terhadap kesiapan berwirausaha; 2) Efikasi diri berpengaruh terhadap kesiapan berwirausaha; dan 3) motivasi berwirausaha berpengaruh terhadap kesiapan berwirausaha. Selain dari 3 variabel exogen ini, masih banyak faktor lain di antaranya yang mempengaruhi kesiapan berwirausaha dimana diantaranya yaitu pengetahuan kewirausahaan, pengalaman prakerin, peran orang tua, dan minat berwirausaha.